A Development Model for the Ogoh-Ogoh Museum in Mengwi Village: Strengthening Sustainable Cultural Tourism in Bali - I Made Bayu Wisnawa; I Made Suwitra Wirya; I Made Hedy Wartana; Putu Bagus Suthanaya; Ida Ketut Kusumawijaya; I Ketut Yudana Adi; Ni Nyoman Nidya Trianingrum; I Ketut Eli Sumerta; Ni Luh Puspa Gayatri; Dimas Dwi Nanda; Maria Triquerta Ngadha; A. A. Ayu Angelina Fitri (Tourism and Hospitality Insights, 2026)
Introduction: Cultural tourism plays an important role in supporting sustainable tourism development by integrating cultural preservation with economic and social benefits for local communities. In Bali, ritual-based arts such as Ogoh-Ogoh represent a unique cultural asset; however, their temporality limits their educational and economic utilization. The establishment of the Ogoh-Ogoh Museum in Desa Mengwi represents an innovative effort to transform ritual art into a permanent cultural tourism attraction. This study aims to analyze and formulate a conceptual model for the development of the Ogoh-Ogoh Museum in Desa Mengwi as a sustainable cultural tourism attraction. Methods: This research employs a qualitative descriptive approach with a case study design. Data were collected through direct observation, in-depth interviews with museum managers and village stakeholders, and documentation review. The data were analyzed using SWOT analysis to identify internal strengths and weaknesses as well as external opportunities and threats influencing the museum’s development. Results: The results indicate that the Ogoh-Ogoh Museum possesses strong cultural value, unique collections, and community-based management through the involvement of the traditional village institution (BUPDA). However, the museum faces challenges related to limited digital promotion, human resource capacity, and operational sustainability. Based on the SWOT analysis, strategic alternatives were formulated through SO, WO, ST, and WT strategies, which were then synthesized into a conceptual development model. Conclusion: The study proposes a conceptual model based on four interrelated pillars: cultural preservation, community-based institutional strengthening, interpretation and educational development, and digital tourism adaptation. This model emphasizes that sustainable development of a ritual-based museum should prioritize cultural conservation and institutional stability alongside adaptive tourism strategies. The findings contribute theoretically to cultural tourism and museum studies and practically provide strategic guidance for museum managers and local stakeholders in developing sustainable cultural tourism destinations.